THE EFFECT OF SHIELDING GAS COMPOSITION ON MICROSTRUCTURE AND ABRASIVE WEAR RESISTANCE FABRICATED WITH PTA ALLOYING TECHNIQUE - Cay, V. V.; Ozan, S.; Gok, M. S.; Erdogan, A. (Polska Akad Nauk, Polish Acad Sciences, Inst Metall & Mater Sci Pas, 2013)
In this study, SAE 1020 steel surfaces were separately alloyed with preplaced high-carbon-ferro-chromium (FeCr), ferro-molybdenum (FeMo) and ferro-titanium (FeTi) powders by using plasma transferred arc (PTA) heat source. By using three different types of shielding gas compositions during the alloying process, the study investigated the effects of modified shielding gas composition on the microstructure, hardness, and abrasive wear resistance of specimens. The most homogenous microstructure and the highest wear resistance was obtained in the gaseous environment which included 3% of H-2. Increasing this rate to 5 % in the shielding gaseous composition caused gaps and pores in the microstructure and caused a decrease in the wear resistance. The x-ray examinations of the specimens identified ferro-molybdenum and ferro-titanium solid solutions, ferrit, austenite and martensite phases in their microstructure as the first phase and FeC, Cr7C3, Cr3C2, Fe3C, Fe7C3, MoC and TiC phases as the second phase. As a result, it was concluded that changes in shielding gas composition in surface alloying process affected specimens' microstructure and abrasive wear properties.
Keywords: Surface modification; shielding gas; PTA; alloying; microstructure